Bimbingan Konseling Dalam Krisis Identitas Dan Budaya: Pendekatan Multikultural Dan Penerapannya - Arini, Larasuci; Firman, Firman; Neviyarni, Neviyarni (UNIVERSITAS SERAMBI MEKKAH, 2025)
The increasing complexity of multicultural societies has heightened the prevalence of identity and cultural crises, particularly among individuals from minority groups. This literature review explores the role of multicultural counseling in addressing identity crises and cultural conflicts, focusing on the effectiveness of culturally competent counseling approaches. Utilizing theories of acculturation (Berry, 2005) and identity development (Erikson, 1968), the study highlights the critical importance of counselor competence in understanding and integrating clients’ diverse cultural backgrounds. Results indicate that identity crises often arise from the pressure to assimilate into dominant cultures while preserving one’s cultural heritage, leading to psychological distress. Multicultural counseling approaches, which emphasize respect for cultural differences and personalized counseling strategies, are shown to be effective in helping clients resolve these crises. However, significant challenges remain, particularly in the training and practice of multicultural counseling. Counselors often lack sufficient skills to manage complex cultural issues, underscoring the need for enhanced multicultural competence in counseling education. The review concludes that adopting an integrative acculturation strategy, in which individuals maintain their cultural identity while adapting to new cultural environments, significantly improves psychological well-being. This study provides practical implications for the development of multicultural counseling practices and suggests directions for future research to bridge the gap between theory and practice in addressing identity crises in multicultural settings.